Names of Buildings in the Surakarta Hadiningrat Kasunanan Palace: A Study of Cultural Semantics - Manumanasa, Sindhu Linguistika; Sumarlam, Sumarlam; Rais, Wakit A. (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to descript the cultural meaning of the name of the building in the Surakarta Hadiningrat Kasunanan Palace. This research is qualitative descriptive. Data source and data are the names of buildings that have cultural significance. Data collection uses observation methods with recording and listening techniques, interview methods, and document analysis methods. The method of presenting the results of the data analyst uses formal and informal methods. The results of the study found 19 names of buildings that have cultural significance in them, namely Tugu Pamandêngan, Gapura Pamurakan, Grand Mosque, North Pagongan Ward and South Pagongan Ward, Suméwa Gymnasium, Sitinggil Lor, Manguntur Tangkil Ward, Talang Patén College, Sri Manganti Lor, Sasana Séwaka, Paningrat Ward, Dalêm Agêng Prabasuyasa, Sangga Buwana Stage, Bêdhaya Ward, Argapura, Sanga Well, West Kêraton in Prabasana, and Ivory Coast.